Practical Aspects of Cylinder Deactivation and Reactivation - Norbert Zsiga (Energies, 2021)
Cylinder deactivation is an effective measure to reduce the fuel consumption of internal combustion engines. This paper deals with several practical aspects of switching from conventional operation to operation with deactivated cylinders, i.e., gas spring operation with closed intake and exhaust valves. The focus of this paper lies on one particular quantity-controlled stoichiometrically-operated engine where the load is controlled using the valve timing. Nevertheless, the main results are transferable to other engines and engine types, including quality-controlled engines. The first aspect of this paper is an analysis of the transition from fired to gas spring operation, and vice versa, as well as the gas spring operation itself. This is essential for mode changes, such as cylinder deactivation or skip-firing operation. Simulation results show that optimizing the valve timing in the last cycle before deactivating/first cycle after reactivating a cylinder, respectively, is advantageous. We further show that steady-state gas spring operation is reached after approximately 6 s regardless of the initial conditions and the engine speed. The second aspect of this paper experimentally verifies the advantage of optimized valve timings. Furthermore, we show measurements that demonstrate the occurrence of an unavoidable torque ripple, especially when the transition to and from the deactivated cylinder operation is performed too quickly. We also confirm with our experiments that a more gradual mode transition reduces the torque drop.